Carbon assimilation and habitat segregation in resurrection plants: a comparison between desiccation‐ and non‐desiccation‐tolerant species of Neotropical Velloziaceae (Pandanales). (27th May 2015) - Alcantara, Suzana; de Mello‐Silva, Renato; Teodoro, Grazielle S.; Drequeceler, Kamila; Ackerly, David D.; Oliveira, Rafael S.
Summary: Desiccation tolerance is the ability that some organisms show to equilibrate their water content with that of dry air and recover when water supplies are re‐established. This is a widespread although rare strategy in angiosperms, and most desiccation‐tolerant (DT) species are restricted to tropical rock outcrops. Such restricted ecological range is attributed to weak competitive potential caused by low productivity, due to the temporal limitation in carbon assimilation that occurs when plants desiccate. However, few studies addressing this question in angiosperms have been conducted. We investigate 20 species of Velloziaceae of campos rupestres that differ in their desiccation tolerance. Campos rupestres is an ecoregion characterized by particular vegetation growing on rocky substrates that occurs along mountains in central/south‐eastern Brazil, above 900 m a.s.l. It is considered a Neotropical hotspot and the main centre of diversity for DT vascular plants and the Velloziaceae. Here, we tested whether carbon assimilation rates, functional traits and species habitats corroborate the hypothesized trade‐off between productivity and desiccation tolerance. All species showed similar photosynthetic rates during the wet season; in the dry season, only DT species showed drastic decrease in their metabolism. Non‐desiccation‐tolerant (NT) species are larger than DT ones (i.e. greater maximum plant height; stem volume). Relative canopy area and stem dry‐matter content were lower in DT compared to NT, while leaf phosphorous concentration was higher in DT. The remaining morphofunctional traits evaluated did not vary between these groups. DT species occupied mainly exposed rock soils, while NT species occurred in deep, sandy soil habitats. Our results support the hypothesis of a trade‐off between desiccation tolerance and productivity in angiosperms and suggest that DT strategy may only evolve and persist in habitats where severe growth limitations due to drought limit competition from more productive species. Abstract : Lay Summary